Interventions to modify the habituation of biological responses to repeated stress in healthy adults: a randomized controlled trial - Janson-Schmitt, Johanna; Rohleder, Nicolas (Trials, 2024)
Background: Changes in response patterns of biological stress systems, including responses of the sympathetic nervous system (SNS) and the hypothalamus–pituitary–adrenal (HPA) axis to repeated stress, can promote the development and progression of chronic diseases via changes in downstream inflammatory processes. The aim of this project is thus to investigate, whether habituation of biological stress system activity including responses of the inflammatory system can be modified. Aiming to test for possible paths of action, a randomized controlled study with two intervention programs designed to manipulate cognitive coping strategies will be carried out. By increasing either ruminative or self-compassionate thoughts among healthy young adults, the intervention programs are expected to affect the regulation of occurring emotions as expressed by the responsiveness of biological systems during repeated stress exposure. Methods: In this study, a total of 120 healthy adults will complete the Trier Social Stress Test (TSST) on two consecutive days. Immediately after the first stress induction, participants will be randomly assigned to two experimental conditions designed to manipulate cognitive coping strategies (rumination vs. self-compassion) or a control condition. Measures of HPA axis (salivary cortisol) and autonomic activity (salivary alpha amylase, heart rate, heart rate variability) as well as inflammatory markers (plasma interleukin(IL)-6, expression rates of pro- and anti-inflammatory cytokine genes) will be repeatedly assessed throughout the experimental sessions. Response and habituation indices of these measures will be calculated and compared between the experimental conditions and the control condition. Discussion: The results should provide insight into whether modifying response patterns of biological stress systems could reverse a significant biological mechanism in the development of stress-related diseases. Trial registration: German Clinical Trials Register (DKRS), DRKS00034790. Registered on August 12, 2024, https://www.drks.de/DRKS00034790.
CRIS-Team Scopus Importer:2024-11-29
Keywords: Allostatic load; Gene expression; Habituation; Inflammation; Repeated stress; Rumination; Self-compassion; Stress response patterns